Operating Performance of Go Public Retailer Companies - Artha Erlina G. Simamora (Universitas Trisakti, 2007)
The general objective of this study is to identify correlation between operating performance of retail industries, in this study acts as dependent variable (Y), and number of financial ratio acts as independent variable (X) covering current ratio (X1), debt ratio (X2), total asset turover (X3) and operating profit margin (X4). Result of this study shows that based on correlation coefficients, there is no a significant correlation between current ratio, total assets turnover. operating profit margin and return on assets. Only debt ratio has significant correlation with return on assets. Upon the result above. retail companies are required to make solid calculation for opeation.